Efficiency assessment of microplastic extraction from green mussel Perna viridis Linnaeus - Oanh, Doan Thi; Thuy, Duong Thi; Huong, Nguyen Thi Nhu; Quynh, Hoang Thi; Nguyet, Vu Thi; Nam, Phuong Ngoc; Tuan, Pham Quoc; Thinh, Ngo Thi Xuan; Thuong, Bui Huyen; Quynh, Le Thi Phuong (Academia Journal of Biology, 2021)
Microplastics with particle size less than 5 mm are becoming a raising global environmental crisis. These pollutants were found from the poles to the equator, in continental shelves, coasts and in the oceans, moreover, they have also been identified in the water columns, sediments and even in a variety of organisms. The majority of microplastics that ended up in the oceans originate from the land. Due to their small size, they are easily accumulated in the food chain, causing harmful effects on organisms and human health. The bivalves especially caught the interest of scientific researchers because of their direct contact with microplastics through the filter-feeding habit. Therefore, it is essential to develop methods to determine the presence of microplastics in these organisms and identify their source. This study evaluated the efficiency of extracting microplastics from the tissues of green mussels (Perna viridis) using KOH 10% solution to digest and KI 50% as the separating solution. Mussel soft tissue samples were spiked five different types of microplastics: polystyrene (PS), polyvinyl chloride (PVC), polyethylene terephthalate (PET), polypropylene (PP), high-density polyethylene (HDPE) and treated with KOH 10% solution and KI 50% solution. The presence of microplastics in some green mussel species was also investigated in some mussel farming areas in Giao Thuy, Nam Dinh province, Thi Nai, Quy Nhon, Binh Dinh province and Hue city, Thua Thien Hue province. The research results showed high efficiency of microplastic extraction and recovery with the range from 76% to 97%. Microplastic concentration obtained in all mussel samples variates from 1.0 ± 0.1 particles/g to 1.7 ± 0.6 particles/g, in which fiber microplastics predominated. Microplastics in mussel samples have small sizes of < 1,000 µm and 1,000–2,000 µm, make up 74.15–82.32% and 9.76–14.71%, respectively. Purple was dominant among all mussel samples. This study proved that using KOH 10% solution and KI 50% solution to isolate microplastics is a suitable approach and can be used in monitoring studies of microplastic pollution in bivalves.